Identification of epigenetic methylation silencing in diffuse large B cell lymphoma in East Coast Malaysia - Lailatul Jalilah Mohd Ridah (Kulliyyah of Allied Health Sciences , International Islamic University Malaysia, 2016)
Diffuse large B cell lymphoma (DLBCL) is the most common type ofnon-Hodgkin's lymphoma. It is a high grade NHL with heterogeneityobserved in the morphologic appearance, immunophenotype, molecular pathogenesis and response to treatment. Epigenetic methylationhas been implicated in its pathogenesis and has become a topic of considerable interest in the past few years. In Malaysia, there is very minimal dataon prevalence of gene methylation in DLBCL. Hence,this study investigatedthe methylation status of p16, MGMT and SPOCK2. p16 tumor suppressor gene inhibits cyclin-dependent kinase,which results inphosphorylation of retinoblastomaand blockage of cell cycle at G1 phase. DNA repair gene MGMT removes and transfers alkyl adduct at O6-guanine to a cysteine residue within the protein, thus preventing lethal cross-links.SPOCK2, an extracellular chondroitin and heparin sulfate proteoglycans, functions mainly in extracellular matrix for cell adhesion. SPOCK2, whichencodes for testican 2,abolishes the inhibition of membrane-type 1-matrix metalloproteinase by other testican family which might enhance the angiogenesis.Hence, the absence of SPOCK2 methylation in the majority of cases was hypothesized to be observed. Aberrantly methylatedp16 and MGMThave been linked to DLBCL, but not SPOCK2. In this study, the extracted genomic DNA from 88 formalin-fixed paraffin embedded tissues of DLBCL and five normal lymph nodes were subjected to bisulfite conversion followed by methylation-specific PCR (MSP) analysis for p16, MGMT and SPOCK2 methylation. Next, p16 methylation was quantified in 16 samples through pyrosequencing assay.Due to unsuccessfulness in primer design, quantitative evaluation was not able to be performed for MGMT and SPOCK2. SPSS version 12.0 was utilised to perform the statistical analysis accordingly. p16 methylation was spotted in 65/88 (74%) samples by MSP. Pyrosequencing detected p16 methylation in all 16 samples ranging from 18% to 81%. In 6 of the 16 samples MSP failed to identify the DNA methylation. MGMT methylation was detected in all 88 (100%) cases. On the other hand, methylatedSPOCK2 was found in 83 (94.3%) samples. There was a significant association between p16 methylation status with patients aged >50 years old (p= 0.04). This study indicates the contribution of p16and MGMTmethylation in DLBCL. Poor expression of p16is believed totriggeran inappropriate cell cycle and consequently cancer cells development. According to previous report, hypothetically, unhealthy lifestyle might affect the percentage of MGMT methylation in this study population. On the contrary,as only five (5.6%) cases were found to be unmethylated for SPOCK2, then the finding seems not to be in parallel with earlier hypothesis.These preliminary discoveriesmay serve as a good platformin order to gain a comprehensive overview on the epigenetics contribution in the pathogenesis of DLBCL. The results also show that pyrosequencing is a robust tool in detecting and quantifying methylation.